PROBLEMATIKA DAN TANTANGAN PENDIDIKAN ISLAM DI INDIA - Annisa Tri Rezeki; Aslan Aslan (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
The history of Islam's entry into India is a long journey that began in the 7th century when Prophet Muhammad SAW was still alive. Starting from Arab trade, which was not only focused on physical commodities but also served as a means of Islamic preaching. The influence of Islam strengthened with the arrival of Arabs who settled and formed kingdoms in India. Subsequently, the arrival of the British as traders resulted in tensions between Islam and Hinduism, as well as a renewal movement within the Muslim community. The renewal movement gave birth to key figures that played pivotal roles in India's social and political history. Furthermore, Islamic education in India underwent significant and inclusive developments, collaborating with national and international curricula. Islamic higher education institutions in India also gained global recognition, competing with leading universities. All of these illustrate the significant role of Islam in India's history and development.